HERA results on the structure of the proton - Foster, B (2003)
A selection of results from the H1 and ZEUS experiments at HERA are reviewed, particularly in the area of deep inelastic scattering and diffraction. Quantum chromodynamics gives a good explanation of these data down to surprisingly low values of the four-momentum transfer, Q(2). Data at smaller Q(2) can be described by Regge models as well as by dipole models including parton-saturation effects. The latter can also give a unified description of many features of diffractive data.